ANISOTROPY STUDY OF THE FEBRUARY 4TH 2008 SWARM IN NW PELOPONNESUS (GREECE) - Kaviris, G.; Papadimitriou, P.; Makropoulos, K. (Bulletin of the Geological Society of Greece, 2010)
The Gulf of Corinth, located in central Greece, is characterized by normal faulting and by high seismicity since the antiquity. On 4 February 2008 a seismic swarm burst in NW Peloponnesus characterized by the occurrence of two moderate-size earthquakes of moment magnitudes 4.7 and 4.5, respectively. Analysis of the data revealed the existence of shear-wave splitting. The events that were chosen for the anisotropy study fit the selection criteria, having clear and impulsive S wave arrival phases on the horizontal components. In addition, the amplitude of the S wave phase on the vertical component was smaller than on the horizontal ones. The representations that were used to determine the polarization direction of the fast split shear wave, the time delay between the two split shear waves and the polarization direction of the source were the polarigram and the hodogram. The uniform fast shear wave polarizations, irrespective of the azimuth of each event, are consistent with the general NNE-SSW direction of extension in the Gulf and, therefore, in agreement with the extensive dilatancy anisotropy (EDA) model. Finally, a decrease of the time delay values was observed after the occurrence of the first moderate earthquake, implying changes of the medium’s properties.